Assessment of Electronic Ticket Law (ETLE) Against Four-Wheeled Road Users in the Area of the Traffic Directorate of Polda Metro Jaya - Erika Kusuma Rahmadany; Feny Windiyastuti (IHSA Institute, 2022)
Users of four-wheeled vehicles in everyday life can have a negative impact, namely traffic jams and accidents, requiring law enforcement efforts by using an electronic ticket or called ETLE. The application of ETLE is a new thing in traffic law enforcement at the Traffic Directorate of Polda Metro Jaya. the enactment of electronic ticketing can provide fast and effective service so as to provide convenience in resolving traffic violations. Electronic Traffic Law Enforcement is the implementation of technology to record violations in traffic electronically to support security, order, and safety. ETLE provides a guarantee of the application of the law for all parties participating in traffic, especially four-wheeled motorists. The electronic ticket does not present officers in the field but monitors through a monitoring camera, later traffic riders who violate will be told what the sanctions in accordance with the violation are made through a letter sent to the address of the violator.